Unravelling the electrochemical impedance spectroscopy of hydrogenated amorphous silicon cells for photovoltaics - Soni Prayogi; Deril Ristiani; D. Darminto (Materials for Renewable and Sustainable Energy)
Abstract This research reveals the application of electrochemical impedance spectroscopy (EIS) in analyzing and improving the performance of hydrogenated amorphous silicon (a-Si: H) based photovoltaic cells. As a non-destructive technique, EIS provides deep insight into the electrochemical characteristics of photovoltaic cells, including series resistance, layer capacitance, recombination mechanisms, and charge transport. The impedance data is obtained and analyzed using small AC potential signals at various frequencies via Nyquist diagrams and Bode plots. This analysis allows the identification of resistive and capacitive elements as well as the evaluation of the quality of the interface between the active layer and the electrode. The results show that EIS can identify internal barriers that reduce the efficiency of a-Si: H solar cells, such as dominant recombination mechanisms and inefficient charge transport. Using equivalent circuit models, electrochemical parameters are extracted to reveal cell behavior and performance. In addition, these results also confirm that EIS is an important tool in design optimization and performance improvement of a-Si: H photovoltaic cells, providing a solid scientific basis for the development of more efficient and sustainable solar cell technology. These findings contribute to efforts to increase solar energy efficiency, supporting broader and more effective use of photovoltaic technology in meeting global sustainable energy needs.